Selective oral ROCK2 inhibitor down-regulates IL-21 and IL-17 secretion in human T cells via STAT3-dependent mechanism. - Zanin-Zhorov, A; Weiss, J; Nyuydzefe, MS; Chen, W; Scher, J; Mo, R; Depoil, D; Rao, N; Liu, B; Wei, J; Lucas, S; Koslow, M; et al. (National Academy of Sciences, 2014)
Rho-associated kinase 2 (ROCK2) regulates the secretion of proinflammatory cytokines and the development of autoimmunity in mice. Data from a phase 1 clinical trial demonstrate that oral administration of KD025, a selective ROCK2 inhibitor, to healthy human subjects down-regulates the ability of T cells to secrete IL-21 and IL-17 by 90% and 60%, respectively, but not IFN-γ in response to T-cell receptor stimulation in vitro. Pharmacological inhibition with KD025 or siRNA-mediated inhibition of ROCK2, but not ROCK1, significantly diminished STAT3 phosphorylation and binding to IL-17 and IL-21 promoters and reduced IFN regulatory factor 4 and nuclear hormone RAR-related orphan receptor γt protein levels in T cells derived from healthy subjects or rheumatoid arthritis patients. Simultaneously, treatment with KD025 also promotes the suppressive function of regulatory T cells through up-regulation of STAT5 phosphorylation and positive regulation of forkhead box p3 expression. The administration of KD025 in vivo down-regulates the progression of collagen-induced arthritis in mice via targeting of the Th17-mediated pathway. Thus, ROCK2 signaling appears to be instrumental in regulating the balance between proinflammatory and regulatory T-cell subsets. Targeting of ROCK2 in man may therefore restore disrupted immune homeostasis and have a role in the treatment of autoimmunity.